Hubungan Fleksibilitas serta Keseimbangan dan Kekuatan Genggaman dengan Hasil Memanjat Nomor Boulder - Shafari, Hilman Abdurrahman; Berliana, Berliana; Sartono, Hadi; Pitriani, Pipit (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2023)
In a certain sport side by side with supporting physical conditions as is the case in rock climbing especially boulder numbers, physical conditions such as flexibility, balance and grip strength have an impact on the final result of a climb. This study aims to determine the relationship between flexibility and balance and strength. Hands on Results of Climbing Number Boulder UKM PAMOR FPOK UPI. Quantitative correlation method. The method used is correlation analysis with only one treatment meeting. Quantitative correlation research design. The method used is correlation analysis with only one treatment meeting. The subjects of this study were 9 athletes in the climbing division of UKM PAMOR FPOK UPI. The instruments used in this study were the V-Sit and Reach test, to determine a person's level of muscle flexibility, Standing Stroke to determine a person's balance level and the Handgrip Dynamometer to measure the level of hand muscle strength. The Sig F Change value and the R square value (Correlation Coefficient) in athletes with high scores Show a significant and strong relationship simultaneously between flexibility, balance, and grip strength on the results of climbing the Boulder UKM PAMOR FPOK UPI. Thus it can be concluded that there is a relationship between flexibility and balance as well as grip strength on the results of climbing the Boulder Number UKM PAMOR FPOK UPI.